Assessment of Seaweed Farming Suitability in Tesabela Village Kupang Regency Using Geographic Information System - Nuban, Sri Rahayu; Rina, Timotius Ragga; Khairani, Nurul Fitri; Bulan, Melkianus Teddison; Malafu, Norsem Nehemia; Banggut, Emanuel Destianus; Lukmini, Aisyah; Swari, Wahyu Dani; Rassi, Sakeos Mullia; Bota, Bernadus (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
Seaweed plays an important role in the implementation of the Blue Economy concept in Indonesia, as it not only serves as a commodity that supports the economy of coastal communities, but also has the potential to enhance national food security, mitigate the impacts of climate change, and promote sustainable marine resource management practices. The waters of Tesabela Village represent one of the potential areas that can be developed as a seaweed aquaculture center in Kupang Regency. The purpose of this research is to generate a site suitability map for seaweed cultivation in the marine area of Tesabela Village, Kupang Regency. Sampling points were determined using purposeful random sampling, but within the entire area. A total of six sample points were selected. Sample points one through six represent the waters of Tesabela Village. Secondary data was also collected to provide additional information for the geographic information system. The analysis showed that three stations were categorized as highly suitable (S1): stations 4, 5, and 6, with a total area of ​​96.57 ha. Stations 1, 2, and 3 were categorized as suitable (S2), or acceptable, with an area of ​​80.48 ha. These factors have the potential to reduce productivity, but farmers can generally address them through technical adjustments. Furthermore, seaweed farmers still need more support from the government and the private sector to maintain the sustainability of their farming operations and to conduct further research.